2022
DOI: 10.22161/ijllc.2.6.3
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement and its influence in boosting productivity

Abstract: Today's managers are working hard to improve their performance in the face of increasing competition and obstacles. Organizational objectives can only be met if employees are engaged with their jobs. In addition, they indicated that further research is needed to determine how it affects performance. Emotional involvement in the workplace can be described as "putting one's heart and soul into one's work. The study aimed to investigate the impact of work engagement on boosting productivity at selected private bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…The analysis employed panel data to test its assumptions through the use of fixed and random effect models and methods . Using metrics like return on assets, return on equity, and earnings per share of net income (Abdulrahman et al, 2022), the study found that capital structure as assessed by assets and liabilities had a positive and statistically significant effect on banks in Jordan . In terms of land rights in relation to assets, the results showed a positive effect and a sizable return on assets, as well as an unfavorable impact of statistical significance on both earnings per share of net profit and return on equity , whereas bank size has a statistically positive effect on bank profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis employed panel data to test its assumptions through the use of fixed and random effect models and methods . Using metrics like return on assets, return on equity, and earnings per share of net income (Abdulrahman et al, 2022), the study found that capital structure as assessed by assets and liabilities had a positive and statistically significant effect on banks in Jordan . In terms of land rights in relation to assets, the results showed a positive effect and a sizable return on assets, as well as an unfavorable impact of statistical significance on both earnings per share of net profit and return on equity , whereas bank size has a statistically positive effect on bank profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…KM is able to facilitate the execution of the majority of the business procedures that are typically carried out. The study assumed that the structure of work behavior was the only factor that had any impact on any aspect of work, including their presence and level of relevance (Abdulrahman et al, 2022).Al-Emran et al (2018), on the other hand, analyzed the link between the production of employee creativity and overall efficiency . This was done when the authors were examining how specific work qualities, such as innovation and employee growth, impact one another .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The difficulty in estimating relationships between various variables that are prone to shifting and switching over different time periods is typically limited to the dispersion of different sources of data and expertise, which frequently contain a high degree of risk as well as information that can be used in decision-making (Abdulrahman et al, 2022). This is because various variables are susceptible to shifting and switching over different time periods .…”
Section: Theoretical Backgroundmentioning
confidence: 99%